Analysis of the Pseudomonas aeruginosa Regulon Controlled by the Sensor Kinase KinB and Sigma Factor RpoN - Damron, F. Heath (American Society for Microbiology, 2012)
Alginate overproduction by Pseudomonas aeruginosa, also known as mucoidy, is associated with chronic endobronchial infections in cystic fibrosis. Alginate biosynthesis is initiated by the extracytoplasmic function sigma factor (σ(22); AlgU/AlgT). In the wild-type (wt) nonmucoid strains, such as PAO1, AlgU is sequestered to the cytoplasmic membrane by the anti-sigma factor MucA that inhibits alginate production. One mechanism underlying the conversion to mucoidy is mutation of mucA. However, the mucoid conversion can occur in wt mucA strains via the degradation of MucA by activated intramembrane proteases AlgW and/or MucP. Previously, we reported that the deletion of the sensor kinase KinB in PAO1 induces an AlgW-dependent proteolysis of MucA, resulting in alginate overproduction. This type of mucoid induction requires the alternate sigma factor RpoN (σ(54)). To determine the RpoN-dependent KinB regulon, microarray and proteomic analyses were performed on a mucoid kinB mutant and an isogenic nonmucoid kinB rpoN double mutant. In the kinB mutant of PAO1, RpoN controlled the expression of approximately 20% of the genome. In addition to alginate biosynthetic and regulatory genes, KinB and RpoN also control a large number of genes including those involved in carbohydrate metabolism, quorum sensing, iron regulation, rhamnolipid production, and motility. In an acute pneumonia murine infection model, BALB/c mice exhibited increased survival when challenged with the kinB mutant relative to survival with PAO1 challenge. Together, these data strongly suggest that KinB regulates virulence factors important for the development of acute pneumonia and conversion to mucoidy.